Pengaruh Kualitas Produk dan Persepsi Harga terhadap Keputusan Pembelian Produk CV. Sinar Fajar Aluminium dan Kaca di Kota Kediri - Lathifah, Mazaya Nur; Zawawi, Zawawi (Jurnal EMT KITA, 2026)
This study aims to determine how consumers choose to purchase products at CV. Sinar Fajar Aluminum and Glass in Kediri based on their perceptions of price and product quality. The basis of this study is the decline in sales performance experienced by the company due to weak marketing strategies and competition in price and product quality in the building materials sector. This study employed a quantitative survey method; incidental sampling was used to distribute questionnaires to 80 participants. Structural Equation Modeling (SEM), focusing on Partial Least Squares (PLS), was used to analyze the data. The results of this study indicate that perceptions of product price and quality play a positive and significant role in consumer purchasing decisions. These findings suggest that improving product quality, particularly in terms of design and durability, as well as adjusting prices in line with perceived benefits, can encourage consumers to make purchasing decisions. This research has practical benefits for businesses in developing more efficient marketing strategies to increase competitiveness and enhance customer loyalty.